Costs of administration, travelling, and productivity losses associated with hospital administration of multiple myeloma drugs in Finland. (3rd April 2019) - Mankinen, Petri; Vihervaara, Ville; Torvinen, Saku; Martikainen, Janne; Soini, Erkki
Abstract: Aim: To estimate the drug administration, travelling, and productivity costs associated with infusion or subcutaneous proteasome inhibitor (PI) treatments (specifically carfilzomib and bortezomib) for multiple myeloma (MM) patients in Finland. Materials and methods: Price tariffs of Finnish hospital districts are used as the basis of invoicing sent to healthcare service payers. A review of these price tariff lists was conducted and obtained data analysed to estimate the mean unit cost of PI administration visit. Travelling costs stratified by areas with different population densities were assessed, based on the national travelling reimbursement register data maintained by the Social Insurance Institution of Finland. Productivity costs due to time spent on administration visits and travelling were estimated based on an expert interview and a spatial healthcare accessibility analysis. Results: Nineteen (95%) of the Finnish hospital districts were included in the review. Relevant unit cost information was found for 15 (75%) of the districts. The mean PI administration cost alone was 270€ (95% CI = 189€–351€) per administration and increased to 371€ when travelling costs were included. Productivity costs added, the mean PI administration costs totalled 405€ for bortezomib and 437€ for carfilzomib. Limitations: The costing rationale of price tariffs may vary between hospital districts. Productivity costs were estimated conservatively, due to lack of data. Conclusions: The administration of intravenous or subcutaneous PIs to treat MM in healthcare facilities causes significant and potentially avoidable healthcare, travelling, and indirect costs, and they should be included in all health economic evaluations (HEEs). As the cost estimates utilized in this study represent most of central hospitals in the country, they provide useful information for future HEEs. A broader conclusion is that novel oral medications, such as the first oral PI, have a significant potential for reducing administration-related costs of subcutaneous or intravenous PIs.